Peran Hatobangon dalam Mencegah Perceraian di Desa Paolan - Harahap, Nita Novi Yanti; Ahmatnijar, Ahmatnijar (Jurnal El-Thawalib, 2024)
Hatobangon plays an active role in the ongoing process of carrying out marriages, such as deciding various matters regarding customs in marriage and providing various moral advice to the bride and groom and making the event successful so that it runs smoothly until it is finished. Besides that, it turns out that hatobangon also plays a role in solving various household problems that occur in the village of Paolan, especially the problem of divorce. In this study, the focus of research is how the divorce process is and what is the role of hatobangon in preventing divorce in Paolan Village, Halongonan District, North Padang Lawas Regency. This study uses a qualitative approach and the type of research is field research. While the data collection instruments used were interviews and documentation. The type of data used is primary and secondary data. Then do data analysis and drawing conclusions. The conclusion of this study is that the process of solving household problems that often occurs alternatively is played by hatobangon. Hatobangon has a very important role in the process of solving family problems, especially the problem of divorce between husband and wife that occurred in Paolan Village. This role is carried out very well in accordance with its social position in society, this can be seen from the success of the hatobangon in preventing divorce and solving various problems that occur in the household. The researcher stated that the hatobangon has a very important role for the people of Paolan Village, especially in terms of solving divorce problems. The role of hatobangon in Paolan Village is quite effective in solving problems in society, especially related to divorce